Creating a community advisory board for pediatric bladder health - Teehan, Emily; Phord-Toy, Ashley; Venkatapuram, Pranaya; Kan, Kathleen M. (Frontiers in Pediatrics, 2024)
Pediatric lower urinary tract symptoms (LUTS) are highly prevalent in neurologically healthy school-aged children. However, no evidence-based programs exist to prevent or treat LUTS in the community setting. To address this, we established the first community advisory board (CAB) that aims to identify individual and societal structures impacting pediatric bladder health in Northern California’s Bay Area and co-design culturally relevant bladder health interventions. Our final CAB comprised of two parents, two community health workers, one educator, one pediatric urology registered nurse, and one pediatrician. The CAB met quarterly during the 1-year study period where bi-directional feedback identified community-level barriers to bladder health, particularly in the school environment, and the need for tailored resources to teach children and families about healthy bladder behaviors. Consequently, the CAB co-designed school-based bladder health interventions, including bladder health posters, and provided feedback on three school-based research study proposals. The CAB will continue to guide and inform future community-engaged research efforts.